Melt-quenched carboxylate metal–organic framework glasses - Minhyuk Kim; Hwa-Sub Lee; Dong-Hyun Seo; Sung June Cho; Eun-chae Jeon; Hoi Ri Moon (Nature Communications, 2024)
Abstract Although carboxylate-based frameworks are commonly used architectures in metal-organic frameworks (MOFs), liquid/glass MOFs have thus far mainly been obtained from azole- or weakly coordinating ligand-based frameworks. This is because strong coordination bonds of carboxylate ligands to metals block the thermal vitrification pathways of carboxylate-based MOFs. In this study, we present the example of carboxylate-based melt-quenched MOF glasses comprising Mg2+ or Mn2+ with an aliphatic carboxylate ligand, adipate. These MOFs have a low melting temperature (T m) of 284 °C and 238 °C, respectively, compared to zeolitic-imidazolate framework (ZIF) glasses, and superior mechanical properties in terms of hardness and elastic modulus. The low T m may be attributed to the flexibility and low symmetry of the aliphatic carboxylate ligand, which raises the entropy of fusion (ΔS fus), and the lack of crystal field stabilization energy on metal ions, reducing enthalpy of fusion (ΔH fus). This research will serve as a cornerstone for the integration of numerous carboxylate-based MOFs into MOF glasses.